2020
DOI: 10.1016/j.ejim.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The ISTH DIC score predicts outcome in non-septic patients admitted to a cardiovascular intensive care unit

Abstract: Background: The International Society of Thrombosis and Haemostasis (ISTH) disseminated intravascular coagulation (DIC) score is widely used to predict mortality in critically ill -typically septic -patients. The objective of this study was to investigate whether the ISTH DIC-2001 and DIC-2018 score can be used to predict the 30-day mortality in non-septic patients in an intensive care unit (ICU). Methods: In this single-center, prospective observational study we included all patients ≥18 years of age who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Grafeneder et al also demonstrate the power of consecutive coagulation measurements in their study [13]. This finding confirms previous observations that a more dynamic evaluation of coagulopathy may yield a more sensitive measure of ongoing activation of coagulation and DIC [16].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Grafeneder et al also demonstrate the power of consecutive coagulation measurements in their study [13]. This finding confirms previous observations that a more dynamic evaluation of coagulopathy may yield a more sensitive measure of ongoing activation of coagulation and DIC [16].…”
supporting
confidence: 82%
“…In this issue of the European Journal of Internal Medicine Grafeneder et al evaluated the performance of the DIC score in a medical intensive care unit with a focus on cardiovascular diseases [13]. They included 233 patients in their analysis, the majority of which was admitted with acute heart failure, cardiogenic shock, postcardiac surgery, and after cardiopulmonary resuscitation.…”
mentioning
confidence: 99%
“…The ISTH DIC score, which was originally proposed in 2001, integrates routine coagulation parameters: platelet count, elevation of a fibrin-related maker, PT, and fibrinogen level [24]. Although it was initially developed for the diagnosis of overt DIC, there have been emerging evidences showing that the DIC score was able to predict mortality in various clinical settings, for example, in patients with sepsis [25], after cardiac arrest [26], or nonseptic patients in ICU [27]. Previous study in critically ill patients has shown that higher DIC score was associated with major bleeding in those with underlying liver cirrhosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the DIC prevalence had risen from 3.49% in 2015 to 5.58% in 2017. Hjorleifsson and colleagues (2015) retrospectively identified Overt DIC’s occurrence over 5 years as 5% in patients suspected with DIC compared to Grafeneder and colleagues (2020) who applied the ISTH criteria to non-septic patients admitted to a cardiovascular ICU and found Overt DIC rates as9% to 12%in the years 2001 and 2018. Ko and colleagues (2016) reported that the prevalence of DIC assessed by the ISTH criteria was 17.6% in septic shock patients from the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…DIC’s prevalence was found to range from 9.6% to 12.8% in non-septic patients over seven years of follow-up (2001–2018). Still, this low prevalence was associated with an overall mortality of 28% in medical and surgical patients (Grafeneder et al, 2020). Hence, DIC is considered an independent predictor for adverse outcomes and mortality (Gando 2012; Ko et al, 2016).…”
mentioning
confidence: 99%